DEVELOPMENT OF AUGMENTED REALITY DIGITAL MEDIA FOR PATTERNS IN SHAPES AND NUMBERS IN ELEMENTARY SCHOOL - Santiana, Elis; Pranata, Khavisa (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
The main issue in teaching patterns in shapes and numbers at elementary schools is the lack of adequate media to support interactive and visual learning. This research endeavors to create educational media using Augmented Reality (AR) to aid fourth-grade students at SDN Kebon Pala 11 Pagi in recognizing patterns in shapes and numbers. In today's digital landscape, the integration of technology into education is paramount for enriching the learning experience. AR seamlessly merges real-world elements with digital overlays, fostering an immersive and interactive educational environment. The Research and Development (R&D) methodology using the 4D model (Define, Design, Development, Disseminate) is employed in this study . Subsequently, the Design phase involves crafting learning materials aligned with the research objectives. In the Development stage, the AR media was tested and validated by media and subject matter experts. Trials with students and teacher feedback indicated the AR media's effectiveness in helping students understand patterns in shapes and numbers. Results show that AR media increases student engagement and motivation, and aids in comprehending abstract mathematical concepts. Expert evaluations yielded excellent ratings: 94% from media experts, 94% from subject matter experts, 92% from fourth-grade A teachers, 100% from fourth-grade B teachers, and student feedback indicating a "Very Good" qualification. This media is expected to be widely adopted and serve as a reference for developing advanced educational technology in the future.